From Global Learning to National Impact: Penguatan Human Capital, Global Competence, dan Post-Study Contribution Mahasiswa Indonesia di Korea Selatan - Ainur Rofiq; Nuraini Desty Nurmasari; Muhammad Dimar Alam; Hyung Jun Park; A Muhamad Jazuli (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This international community service program aims to enhance the capacity of Indonesian students pursuing higher education abroad through strengthening human capital, career readiness, and post-study contribution orientation. The implementation employed an educational and participatory approach consisting of training sessions, interactive discussions, sharing sessions, and the development of post-study contribution action plans. The target participants were Indonesian students and scholarship recipients currently pursuing their studies at Sungkyunkwan University. The results indicate an increased understanding among participants regarding the importance of human capital development, the strategic role of the academic diaspora in national development, and the opportunities to implement the concept of brain circulation through knowledge transfer, innovation, and global networking. This community service initiative demonstrates that international collaboration based on capacity building can serve as an effective instrument in preparing Indonesian students abroad to make sustainable contributions to national development.